Flow Experience and Behavioral Intentions In K-Pop Concert - Arti Fauziah Khoirunnisa; Ahmad Hudaiby Galih Kusumah (Master of Management FEB ULM, 2026)
This study aims to identify the factors influencing flow experience and its impact on memory and behavioral intentions in the context of K-Pop concerts. This study places greater emphasis on the context of K-Pop concerts, which have distinct characteristics compared to music festivals that are generally the focus of previous research. Using a quantitative approach, data were collected from 309 respondents through a 5-point Likert scale questionnaire with purposive sampling and analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with IBM SPSS Amos 26. The findings reveal that character and visual quality, self-congruence, visitor enthusiasm, and interactions among visitors positively influence flow experience. Furthermore, flow experience significantly impacts memory and behavioral intentions, while memory also contributes to behavioral intentions. This study practical implications for concert organizers and the tourism industry in designing emotional experiences that foster satisfaction and organic promotion, while also expanding the theoretical discourse on flow experience.